Police powers and sexual misconduct: Still keeping the blue code of silence? - Westmarland, Louise (International journal of police science & management, 2025)
This article analyses qualitative data collected as part of a survey using scenarios to discover what respondents thought about certain behaviours and potential misbehaviours carried out by police officers and staff. The data are drawn from a survey that included quantitative and qualitative data collection. We have published the quantitative findings and explored the data in more depth previously. In this article, we concentrate on a specific aspect of the data collected as part of the study; namely, two scenarios from an online survey that have sexual dimensions/connotations. The first scenario asks about unwanted touching and attention, the second about a police officer who has a romantic relationship with the victim of a burglary that he investigated. The discussion poses some questions, and possibly a few tentative answers, about why police officers engage in the types of misconduct that have come to light in recent years and why this misconduct remains hidden in many cases. Increasing amounts of research, and the introduction of police misconduct hearings in public throughout England and Wales, have revealed instances of these types of misbehaviours. The outcomes and penalties involved are also publicly available and some of these are discussed.